OPTIMASI PENGGUNAAN ALAT BERAT PADA PROYEK JALAN TOL GEMPOL-PANDAAN STA 5+500 – STA 11+500 - Muhammad Chrisna Wijaya, Fadjar Purnomo, Adi Muljo (Jurusan Teknik Sipil, Politeknik Negeri Malang, 2015)
Cut and fill is one of the jobs that have to be considered carefully because a lot of heavy equipment is employed. Due to its different capacity, heavy equipment must be carefully and properly selected to maximize its use and minimize the leasing cost. The objective of the study is to find out the optimal time used to operate each heavy equipment, and the leasing cost. The data were of 5 km project span consisting of 1.425 km cut and 4.575 m3 fill, 1,661,104 m3 cut volume and 377,685.9 m3 fill volume. Excavator PC200-8, dump truck Hino FM260 JD, dozer D65PE-12, compactor SD160 were employed during 1,925 hours, total cost of this project IDR 255.125.700.000,00, and percentage of cut and fill cost is 13,496%.First, identifying the work type and work volume was done to determine the suitable heavy equipment used and the number. Second, determining the decision variable, objective function, and problem function, then put them into linear programming. Those data were processed through LINDO program to find out duration and the overall cost of heavy equipment. The analyses result in 4 alternatives. Alternative 2 is of combination of 21 excavators PC200-8, 55 dump truck Hino FM260 JD, 1 dozers D65PE-12, and 2 compactors SD160. 1.902,13 hours duration at IDR 31.369.910.000,00 (thirtysix billion two hundred and twelve million thirtyseven thousand Indonesian rupiah) is chosen or 7%more expensive than contractor price.Keywords: cut and fill, heavy equipment, duration and total cost